Does emotional memory enhancement assist the memory-impaired? - Broster, Lucas S.; Blonder, Lee X.; Jiang, Yang (Frontiers in Aging Neuroscience, 2012)
We review recent work on emotional memory enhancement in older adults and patients with mild cognitive impairment or Alzheimer dementia and evaluate the viability of incorporating emotional components into cognitive rehabilitation for these groups. First, we identify converging evidence regarding the effects of emotional valence on working memory in healthy aging. Second, we introduce work that suggests a more complex role for emotional memory enhancement in aging and identify a model capable of unifying disparate research findings. Third, we identify neuroimaging evidence that the amygdala may play a key role in mediating emotional memory enhancement in mild cognitive impairment and early Alzheimer dementia. Finally, we assess the theoretical feasibility of incorporating emotional content into cognitive rehabilitation given all available evidence.